p16 expression in patient with Loop Electrosurgical Excision Procedure (LEEP) - Paskarani, Putu Erika; Winata, I Gede Sastra; Sitohang, Elisa Laura Oktrinita; Felyanto, Felyanto; Yuliantini, Sang Ayu Putu (Universitas Airlangga, 2024)
HIGHLIGHTS Clinicopathologic characteristic of patient with LEEP procedures dominated by women above 35 years old, with total parity less than 3 and without history of contraceptive usage. The p16 expression analyzed by immunohistochemistry technique. The positive and negative reactivity of p16 ratio was 3:5 on LEEP specimen which microscopically appear as chronic cervicitis, low-grade and high-grade squamous intraepithelial lesion. ABSTRACT Objective: The aim of this study was to reveal p16 expression with the clinicopathological characteristics of patients who underwent cervical biopsy using the Loop electrosurgical excision procedure (LEEP) at Udayana University Hospital, Bali, Indonesia, for the period 2020 – 2023. Materials and Methods: The research was conducted at Anatomic Pathology Laboratory of Udayana University Hospital, Denpasar, Bali, Indonesia. The samples were selected based on inclusion criteria such as the formalin fixed paraffin embedded (FFPE) sample from positive IVA patient and continue for LEEP procedure. Otherwise, the exclusion criteria were moldy FFPE sample and incomplete clinical data. Then, p16 immunostaining procedure was carried out manually. The interpretation of p16 results was analyzed using SPSS software, version 25 by International Business Machines (IBM) Corporation. Results: The positive p16 expression was revealed in 12 samples (38.7%), in contrast the negative staining appeared in 19 samples (61.3%). Unfortunately, p16 expression was not significant statistically based on age, parity, and contraceptive history, with p-values of 1.00, 0.45, and 0.65, respectively. Meanwhile, a statistically significant association was found between p16 expression and histopathologic diagnosis (p = 0.02, 95% CI 1.4 – 38.3). In addition, 22.2% of the variation of p16 expression based on multivariate analysis demonstrating a significant correlation (p = 0.01). Conclusion: p16 expression with histopathology diagnostic characteristic in patient who underwent Loop electrosurgical excision procedure (LEEP) was found statistically significant. Moreover, clinical application of p16 in daily practice should be performed with consideration especially for pre-cancer lesion in LEEP biopsy specimen procedure and clinicopathological approach is essential.